Meningkatkan Hasil Belajar Siswa pada Mata Pelajaran Aqidah Akhlak Melalui Model Pembelajaran Problem Based Learning - Ayyubi, Ibnu Imam Al; Murharyana; Martini, Sofia; Hayati, Ai Faridatul; Apriyanti, Niken Siti Nur; Kamaliya, Shonia (At-Tadris: Journal of Islamic Education, 2024)
This research aims to see whether or not there has been an increase in moral aqidah learning based on the problem-based learning model. Because with problem-based learning students are required to be more contemplative and internalitative in their real lives. This research uses a quasi-experimental research method with a quantitative approach carried out at Roudlotul Ulum Vocational School. The instruments in this research used questionnaires and tests. The test used is a written test in the form of an essay which has been tested for validity, reliability, distinguishing power, and difficulty index. The population of this research were students at Roudlotul Ulum Vocational School with a sample of 30 students in the experimental class and 31 students in the control class in class X on Aqidah Akhlak material. In this research, it was found that learning using Problem-Based Learning (PBL) was better than classes using conventional learning. Apart from that, there is an increase in the learning of moral aqidah and it has a very high effect. This shows that learning moral aqidah using Problem-Based Learning (PBL) is better than conventional learning. So, for previous research, learning differentiation between the PBL learning model and other learning models can be carried out to see whether there are differences or influences in learning aqidah and morals.